ASP Triangles: Sketching the Artificial Intelligence of a Mobile Platform - Di Fraia, Marco (Cranfield University, 2020)
ASP triangles are a tool that we introduced to structure the design process of the on-board Artificial Intelligence (AI) of a mobile platform. Their value lies in taking into account the couplings and interactions between macroelements characterizing the platform and the mission context, in analogy to the paradigm shift introduced in aerospace structures by the development of aeroelasticity.
Keywords: 'DSDS20 Poster'; 'DSDS20'; 'Artificial Intelligence'; 'Robotics'; 'AI Design'; 'Artificial Intelligence and Image Processing not elsewhere classified'